How Binding Are Legal Limits? Transitions from Temporary to Permanent Work in Spain - Maia Güell; Barbara Petrongolo (Institute for the Study of Labor (IZA), 2003)
In the mid-1980s, several European countries, characterized by high levels of employment protection, introduced fixed-term contracts. Since then most accessions to employment have been through fixed-term contracts. This paper studies the duration pattern of fixed-term contracts and the determinants of their conversion into permanent ones in Spain, a country in which the share of fixed-term employment is the highest in Europe. We estimate a duration model for temporary employment, with competing risks of terminating into permanent employment versus alternative states, and flexible duration dependence. We find that the shape of the baseline hazard is suggestive of two possible uses of fixed-term contracts by employers. First, there is a clear, pronounced spike at 3 years of duration, coinciding with the legal maximum duration of these contracts, suggesting that some fixed-term contracts are only converted into permanent ones when there is no other way to retain the worker. Second, there is a spike around 1 year of duration, which supports the idea that some of these contracts are also used as a screening device. Workers who successfully pass the screening may obtain a permanent renewal much before the legal duration limit of their contracts.
Keywords: J60; C41; J41; 330; fixed-term contracts; duration models; Befristeter Arbeitsvertrag; Dauer; Arbeitsverhältnis; Schätzung; Spanien